Guanidinium-Containing Oligomer as an Inhibitor of Microbial Corrosion of Metal - Abdulina, D.R.; Vortman, M.Ya.; Kopteva, Zh.P.; Iutynska, G.O.; Kopteva, A.E.; Lemeshko, V.N.; Shevchenko, V.V.; Biliavska, L.O.; Абдуліна, Д.Р.; Вортман, М.Я.; Коптєва, Ж.П.; Іутинська, Г.О.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Guanidinium-containing oligomers, a poorly studied class of organic compounds, have attracted attention due to their bactericidal properties. A guanidinium-containing oligomer based on an aliphatic oligoepoxide is a newly synthesized substance with bactericidal activity, which gives it the prospects for use as a microbial corrosion inhibitor. Aim. The goal of the study was to synthesize oligomeric alkyl substituted guanidinium bromide and study of its anticorrosive properties in the presence of steel under the influence of corrosive active sulfate-reducing bacteria. Methods. The guanidine-containing alkyl substituted oligomer was obtained by the reaction of the aliphatic oligoepoxide DEG-1 with guanidine, followed by interaction with alkyl bromide. The anticorrosive properties of the guanidine-containing oligomer were studied using collection strains of sulfate-reducing bacteria: UCM B-11503 Desulfovibrio sp.10, UCM B-11501 Desulfovibrio desulfuricans DSM642, and UCM B-11502 Desulfovibrio vulgaris DSM644. The sulfate-reducing bacteria were grown on Postgate В medium for 14 days at a temperature of 28 ± 2 °C. The number of bacteria was determined by the method of tenfold dilution. The corrosion rate was determined by the gravimetric method. The physicochemical parameters of pH and redox potential of the bacterial culture liquid were studied by the potentiometric method. The accumulation of hydrogen sulfide in the culture liquid was determined by the iodometric method. Lipolytic activity was studied spectrophotometrically using a KFK-3 device by reaction with p-nitrophenyl palmitate, catalase activity — using 0.03% hydrogen peroxide, which formed a stable colored complex with a 4% molybdenum diphosphate solution. The specific activity of the studied enzymes was expressed as unit ∙ mg-1 protein. Protein was determined in the supernatant by the conventional Lowry method. Results. It was shown that the oligomer based on aliphatic oligoepoxide has biocidal properties. A significant inhibition of the development of sulfate-reducing bacteria (SRB) was observed after the oligomer was added; only dozens of bacterial cells were detected in the medium after the exposure period. The corrosion rate of steel in the presence of SBR without addition of inhibitors was 0.15 — 0.35 mg/cm2∙h. The addition of DPC (a quaternary ammonium compound based on N-decylpyridinium chloride) (Kyiv Polytechnic Institute (KPI), Ukraine) to the culture medium led to a decrease in the steel corrosion rate to 0.032 — 0.047 mg ∙ cm-2  h-1 (by 6.5—10.6 times). In the presence of Armohib CI-28 inhibitor (based on Diamine Ethoxylate) (Akzonobel, Holland), the corrosion rate was reduced to 0.02—0.039 mg ∙ cm-2  h-1 (by 4.2 — 12.7 times). The addition of guanidinium-containing oligomer to the medium with bacteria reduced the corrosion rate to 0.075—0.079 mg/cm2 ∙ h (by 2.5—2.7 times). According to the mass loss of steel samples, the degree of metal protection against microbial corrosion in the presence of guanidinium-containing oligomer was 60.15—63.17%. Conclusions. The obtained data indicate that the guanidinium-containing oligomer based on aliphatic oligoepoxy has biocidal and anticorrosive properties and is promising for use as a means of combating microbially induced corrosion.